Scenario Analysis in Karlsruhe: Exploring New Argumentative Steps of the Federal Constitutional Court - Giovanni Tuzet; Damiano Canale; Alessio Sardo (German Law Journal)
This Article examines scenario analysis, a disruptive argumentation technique used by the German Federal Constitutional Court (GFCC) in recent high-profile cases, such as the so-called climate protection case (Klimaschutz) and other decisions on the fundamental right to intergenerational justice (Grundrecht auf Generationengerechitgkeit). After explaining the basic argumentative steps involved in scenario analysis, for example designing scenarios, identifying stakeholders, relating scenarios to strategies, determining the main driving forces, estimating scenario probabilities, the Article sketches a normative model for rational scenario design. The normative model is used as a lens for evaluating the arguments developed by the GFCC in the climate protection case. Such evaluation also builds on game-theoretic insights and points out some weaknesses in the Court’s argument. Finally, the Article observes that, as scenario analysis is used to assess the future impact of legislative decisions, it has the effect of imposing greater constraints on legislatures.